(untitled) (GEOmedia, 2023)
As soon as I arrived in Oberkochen, to improve my knowledge of photogrammetry (I was only a good topographer) I was given a small volume entitled "Nur der Name war geblieben" (Armin, 1989): it was the story of the transfer of the famous "Carl Zeiss Stiftung ” ” from Jena to that agricultural village in Swabia, to escape the Soviet ogre. Today, about half a century after those days, I use the Italian version of that title, reduced from the imperfect to the present, to talk about the end of production, by the large German company, of the sector concerning measurement on the ground and on images . Several times I have said and written that human inventions and initiatives generally last a century or so: this is confirmed by the story of the topographical and photogrammetric division of Carl Zeiss: a "season" approximately, in the life of the large company.